2009
DOI: 10.1186/1471-2164-10-266
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interactions modulate the evolution of mammalian mitochondrial respiratory complex components

Abstract: Background: The deleterious effect of a mutation can be reverted by a second-site interacting residue. This is an epistatic compensatory process explaining why mutations that are deleterious in some species are tolerated in phylogenetically related lineages, rendering evident that those mutations are, by all means, only deleterious in the species-specific context. Although an extensive and refined theoretical framework on compensatory evolution does exist, the supporting evidence remains limited, especially fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…In invertebrate PNCs, most interactions are maintained while additional hydrogen bonds and hydrophobic contacts were found. These new interactions might derive from complementary amino acid changes as a result of epistatic interactions between residues [21], [45], which is consistent with a structural conservation of PNCs.…”
Section: Discussionsupporting
confidence: 75%
“…In invertebrate PNCs, most interactions are maintained while additional hydrogen bonds and hydrophobic contacts were found. These new interactions might derive from complementary amino acid changes as a result of epistatic interactions between residues [21], [45], which is consistent with a structural conservation of PNCs.…”
Section: Discussionsupporting
confidence: 75%
“…The software incorporates updated homology modelling methodology [47] for building the human structural models for COI, COII, COIII and CYB. The accuracy of the predicted 3D human models was evaluated in Verify 3D, SOLVX and ANOLEA [48][50].…”
Section: Methodsmentioning
confidence: 99%
“…However, this expectation has been challenged by the realization that there are numerous examples where human mutant alleles correspond to the wild-type alleles in other mammalian species. [1][2][3][4][5][6][7] Such variants have become known as compensated pathogenic deviations (CPDs) following their original designation 5 because it is assumed that the apparently benign nature of these missense variants in non-human species is due to the coexistence of other amino-acid substitutions (AASs) that compensate for their otherwise dysfunctional consequences. Among those human mutant residues corresponding to the wild-type residue in mouse 5 are an p.(Ala53Thr) (NM_000345.3:c.157G4A) substitution at the α-synuclein (SNCA) locus reported to be associated with familial Parkinson disease; 8 the ADA-p.(Arg142Gln) (NM_000022.2: c.425G4A) causing severe combined immunodeficiency; 9 and the CFTR-p.(Phe87Leu) (NM_000492.3:c.259T4C) in the cystic fibrosis transmembrane conductance regulator gene underlying cystic fibrosis.…”
mentioning
confidence: 99%
“…Intriguingly, a different OTC variant p.(Thr125Met) associated with fatal hyperammonemia 14 was found to correspond to the wild-type allele in chimpanzees. 1,15,16 Among the CPDs identified through a comparison with the recently reported mountain gorilla genome 6 was the NPC1-p.(Asn961Ser) (NM_000271.4:c.2882A4G) that leads to Niemann-Pick disease C. 17 Finally, variants associated with ciliopathies at the BBS4 and RPGRIP1L genes associated with Bardet-Biedl and Meckel-Gruber syndromes, respectively, constitute the wild-type alleles in the genomes of several vertebrates. 7 The same study reported a de novo variant at the BTG2 locus in which the disease-associated allele corresponded to the wild-type allele in more than 50 vertebrate species.…”
mentioning
confidence: 99%